Modification of 4-(4-chlorothiophen-2-yl)thiazol-2-amine derivatives for the treatment of analgesia and inflammation: synthesis and in vitro, in vivo, and in silico studies - Mahnashi, Mater H.; Rashid, Umer; Almasoudi, Hassan Hussain; Nahari, Mohammed H.; Ahmad, Imran; Binshaya, Abdulkarim S.; Abdulaziz, Osama; Alsuwat, Meshari A.; Jan, Muhammad Saeed; Sadiq, Abdul (Frontiers in Pharmacology, 2024)
Inflammation is a protective response to a variety of infectious agents. To develop a new anti-inflammatory drug, we explored a pharmacologically important thiazole scaffold in this study. In a multi-step synthetic approach, we synthesized seven new thiazole derivatives (5a–5g). Initially, we examined the in vitro anti-inflammatory potentials of our compounds using COX-1, COX-2, and 5-LOX enzyme assays. After in vitro confirmation, the potential compounds were subjected to in vivo analgesic and anti-inflammatory studies. The hot plate method was used for analgesia, and carrageenan-induced inflammation was also assayed. Overall, all our compounds proved to be potent inhibitors of COX-2 compared to celecoxib (IC50 0.05 μM), exhibiting IC50 values in the range of 0.76–9.01 μM .Compounds 5b, 5d, and 5e were dominant and selective COX-2 inhibitors with the lowest IC50 values and selectivity index (SI) values of 42, 112, and 124, respectively. Similarly, in the COX-1 assay, our compounds were relatively less potent but still encouraging. Standard aspirin exhibited an IC50 value of 15.32 μM. In the 5-LOX results, once again, compounds 5d and 5e were dominant with IC50 values of 23.08 and 38.46 μM, respectively. Standard zileuton exhibited an IC50 value of 11.00 μM. Based on the COX/LOX and SI potencies, the compounds 5d and 5e were subjected to in vivo analgesic and anti-inflammatory studies. Compounds 5d and 5e at concentrations of 5, 10, and 20 mg/kg body weight were significant in animal models. Furthermore, we explored the potential role of compounds 5d and 5e in various phlogistic agents. Similarly, both compounds 5d and 5e were also significantly potent in the anti-nociceptive assay. The molecular docking interactions of these two compounds with the target proteins of COX and LOX further strengthened their potential for use in COX/LOX pathway inhibitions.